Veterinary Cooperative Oncology Group—Common Terminology Criteria for Adverse Events (VCOG‐CTCAE v2) following investigational therapy in dogs and cats. (18th February 2021) - LeBlanc, Amy K.; Atherton, Matthew; Bentley, R. Timothy; Boudreau, C. Elizabeth; Burton, Jenna H.; Curran, Kaitlin M.; Dow, Steven; Giuffrida, Michelle A.; Kellihan, Heidi B.; Mason, Nicola J.; Oblak, Michelle; Selmic, Laura E.; et al.
Abstract: The updated VCOG‐CTCAE v2 guidelines contain several important updates and additions since the last update (v1.1) was released in 2011 and published within Veterinary and Comparative Oncology in 2016. As the Veterinary Cooperative Oncology Group (VCOG) is no longer an active entity, the original authors and contributors to the VCOG‐CTCAE v1.0 and v1.1 were consulted for input, and additional co‐authors sought for expansion and refinement of the adverse event (AE) categories. VCOG‐CTCAE v2 includes expanded neurology, cardiac and immunologic AE sections, and the addition of procedural‐specific AEs. It is our intent that, through inclusion of additional authors from ACVIM subspecialties and the American College of Veterinary Surgery, that we can more comprehensively capture AEs that are observed during clinical studies conducted across a variety of disease states, clinical scenarios, and body systems. It is also our intent that these updated veterinary CTCAE guidelines will offer improved application and ease of use within veterinary practice in general, as well as within clinical trials that assess new therapeutic strategies for animals with a variety of diseases. Throughout the revision process, we strived to ensure the grading structure for each AE category was reflective of the decision‐making process applied to determination of dose‐limiting events. As phase I trial decisions are based on these criteria and ultimately determine the maximally tolerated dose, there is impact on standard dosing recommendations for any new drug registration or application. This document should be updated regularly to reflect ongoing application to clinical studies carried out in veterinary patients.